2011
DOI: 10.1523/jneurosci.0172-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Basis for Opponent Process Mechanisms of Opiate Withdrawal

Abstract: Opponent process theory predicts that the first step in the induction of drug withdrawal is the activation of reward-related circuitry. Using the acoustic startle reflex as a model of anxiety-like behavior in rats, we show the emergence of a negative affective state during withdrawal after direct infusion of morphine into the ventral tegmental area (VTA), the origin of the mesolimbic dopamine system. Potentiation of startle during withdrawal from systemic morphine exposure requires a decrease in opiate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…Previous work from our laboratory and others (Harris and Aston-Jones, 1994;Chartoff et al, 2006;Chartoff et al, 2009;Radke et al, 2011) has demonstrated that dopamine receptor agonists attenuate withdrawal behaviors. The current experiments used two subtype-specific dopamine receptor agonists, SKF82958 and quinpirole, to examine the individual contributions of D1-and D2-like dopamine receptors, respectively, to this effect.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Previous work from our laboratory and others (Harris and Aston-Jones, 1994;Chartoff et al, 2006;Chartoff et al, 2009;Radke et al, 2011) has demonstrated that dopamine receptor agonists attenuate withdrawal behaviors. The current experiments used two subtype-specific dopamine receptor agonists, SKF82958 and quinpirole, to examine the individual contributions of D1-and D2-like dopamine receptors, respectively, to this effect.…”
Section: Introductionmentioning
confidence: 85%
“…Recent work in our laboratory (Radke et al, 2011) supported this prediction by demonstrating that targeted infusion of morphine in the ventral tegmental area (VTA) was sufficient to induce anxiety-like withdrawal behaviors. In the same study, we also found that systemic injection of the general dopamine receptor agonist apomorphine relieved withdrawal-induced anxiety (Radke et al, 2011). Taken together, this evidence led us to hypothesize that negative affective withdrawal behaviors are triggered by declining levels of dopamine in structures downstream of the VTA.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations